دراسة بعض الخصائص الاقتصادية والفنية لتربية الإبل في القطر العربي السوري (Latakia University Journal -Biological Sciences Series, 2019)
استهدفت الدراسة معرفة بعض الخصائص الاقتصادية لتربية الإبل في القطر العربي السوري، والتعرف على بعض الممارسات الفنية لدى مربي الإبل لتشكيل أو تكوين قطيع الإبل في القطر العربي السوري. بالإضافة إلى التعرف على المشكلات التي تواجه مربي الإبل في القطر العربي السوري. ولتحقيق أهداف الدراسة تم تصميم استمارة استبيان بالمقابلة الشخصية حيث بلغ حجم العينة عشرين( 20) مربياً، وتم استخدام الجداول التكرارية والنسب المئوية في التحليل الإحصائي للبيانات. وقد أوضحت النتائج أن نصف المربين(50%) يمتلك قطيعاً صغيراً من الإبل بحجم 100 رأس فأقل، وجميع المبحوثين لا يبيع الحليب، والغالبية العظمى منهم(95%) يستفيد منه في الشرب. كما أن نصف المبحوثين(50%) زاد العائد السنوي لديهم عن 200 ألف ليرة، والغالبية العظمى من المبحوثين(85%) لا يلجأ للوحدات البيطرية وتحصين إبلهم ضد الأمراض. The study aimed to identify the cultural and social phenomena and technical practices of camel breeding in the Syrian Arab republic as well as the problems that face the camel breeders. The study necessitated designing a questionnaire by personally interviewing camel breeders. The total number of completed questionnaires was (20) responses. The most important results of the study are as follow: about (50%) of the respondents owned small cattle (100 and less); all respondents don’t sell their camels’ milk (100%). About (95%) of respondents use the milk for a drink; about (50%) of the respondents received more than two hundred thousand pounds as their annual reward from camels breeding. About (85%) of respondents don’t vaccinate their camels at veterinary units.